2014
DOI: 10.1016/j.juro.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of an Epigenetic Assay to Predict Negative Histopathological Results in Repeat Prostate Biopsies

Abstract: Purpose The DOCUMENT multicenter trial in the United States validated the performance of an epigenetic test as an independent predictor of prostate cancer risk to guide decision making for repeat biopsy. Confirming an increased negative predictive value could help avoid unnecessary repeat biopsies. Materials and Methods We evaluated the archived, cancer negative prostate biopsy core tissue samples of 350 subjects from a total of 5 urological centers in the United States. All subjects underwent repeat biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 25 publications
3
166
0
4
Order By: Relevance
“…In addition to intra/interfocal heterogeneity, a field effect of genetic changes should also be considered because cancer-related genetic changes are also detected in benign areas of the same prostate [99]. This is the underlying premise of new tests designed to predict the risk of finding cancer on repeat biopsy for men with a negative biopsy [79], as well as biopsy-based tissue tests designed to predict whole-gland pathologic features. Genomic analysis of tumor tissue may aid in overcoming the challenges of sampling error and the variability of traditional pathologic grading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to intra/interfocal heterogeneity, a field effect of genetic changes should also be considered because cancer-related genetic changes are also detected in benign areas of the same prostate [99]. This is the underlying premise of new tests designed to predict the risk of finding cancer on repeat biopsy for men with a negative biopsy [79], as well as biopsy-based tissue tests designed to predict whole-gland pathologic features. Genomic analysis of tumor tissue may aid in overcoming the challenges of sampling error and the variability of traditional pathologic grading.…”
Section: Discussionmentioning
confidence: 99%
“…The test achieved a 90% negative predictive value (NPV) within 30 mo of the initial biopsy. In a recent validation trial, 88% NPV was reported, and the test was the most significant predictor of biopsy results [79]. The impact of the epigenetic test on rebiopsy rates was recently surveyed in five centers, and among 138 patients with a negative ConfirmMDx assay, only six patients (4%) underwent repeat biopsies [80].…”
Section: 3mentioning
confidence: 99%
“…The sensitivity and specificity of the assay for the detection of subsequent PCa were 68 and 64 % with negative predictive value (NPV) of 90 % (95 % CI 87-93 %) [28]. Similarly, in a multi-center US study consisting of 350 men receiving repeat biopsy following initial negative biopsy, the methylation assay was associated with a sensitivity of 62 and 64 % and NPV of 88 % (95 % CI 85-91) [29]. A clinical utility field study consisting of patients from five US sites in whom the epigenetic assay had been ordered in the setting of an initial negative prostate biopsy examined the rates of subsequent biopsy.…”
Section: Confirmmdxmentioning
confidence: 95%
“…Выдающиеся результаты были получены A. W. Partin и соавт. [74] при оценке метилирования ДНК генов GSTP1, APC и RASSF1. Это исследование показало, что эпигенетический анализ имеет отрица-тельную предсказательную ценность 88 % и может использоваться в клинической практике.…”
Section: обзорunclassified
“…Авторы считают, что при ком-бинации EVX1 и FGF1 отрицательная предсказательная ценность составила около 91 %, что немногим мень-ше, чем в исследовании A. W. Partin и соавт. [74]. Оче-видно, эти данные будут иметь значимое место в кли-нической практике через несколько лет.…”
Section: обзорunclassified